The Role of Maqasid Shariah Framework in The Management of People with Disabilities (PWD): A Systematic Literature Review - Mohd Nur Hidayat Hasbollah Hajimin; Syamsul Azizul Marinsah; Sarip Adul; Issraq Ramli; Mohd Zohdi Mohd Amin (Human Resource Management Academic Research Society (HRMARS), 2024)
Maqasid Shariah framework is synonymous with the practice of Islamic management to protect the rights and welfare of every human being. This practice is applied to all levels of society regardless of physical condition, to ordinary people or people with disabilities (PWD). Each is entitled to fundamental rights regarding the development of religion, life, intellect, lineage, and wealth. Therefore, this paper will discuss the Maqasid Shariah framework's role in managing PWDs using systematic literature review analysis (SLR). This study uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method by systematically searching articles in the MyCite, MyJurnal and Google Scholar databases from 2012 to 2022. The study found that the Maqasid Shariah framework's role in managing PWD is significant in practice. It fulfills the five main bases (al-daruriyyat al-khams) of PWD inclusively and holistically in self-development: religion, life/health, intellect/education, lineage/dignity and wealth/economics. This study can provide a reference and guidelines to all communities to apply the framework of Maqasid Shariah in the affairs of the management of PWD.